It's not what they do, It's how they do it: Athlete experiences of great coaching - Becker, A. J. (International Journal of Sports Science and Coaching, 2009)
The primary purpose of this study was to explore athlete experiences of great coaching. A total of 18 in-depth phenomenological interviews were conducted with elite level athletes (9 female; 9 male) representing a variety of sports (i.e., baseball, basketball, football, soccer, softball, volleyball, and water polo). Participants ranged in age from 22 to 42 years (M = 29.11, SD = 5.52). Interviews lasted between 30-90 minutes and were transcribed verbatim. Analyses of the transcripts revealed a total of 1,553 meaning units that were further grouped into sub-themes and general themes. This led to the development of a final thematic structure revealing six major dimensions characterizing athlete experiences of great coaching: Coach Attributes, The Environment, Relationships, The System, Coaching Actions, and Influences.